2020
DOI: 10.1371/journal.pone.0237577
|View full text |Cite
|
Sign up to set email alerts
|

Targeting steroid receptor RNA activator (SRA), a long non-coding RNA, enhances melanogenesis through activation of TRP1 and inhibition of p38 phosphorylation

Abstract: Abnormal skin melanin homeostasis results in refractory pigmentary diseases. Melanogenesis is influenced by gene regulation, ultraviolet radiation, and host epigenetic responses. Steroid receptor RNA activator (SRA), a long noncoding RNA, is known to regulate steroidogenesis and tumorigenesis. However, how SRA contributes to melanogenesis remains unknown. Using RNA interference against SRA in B16 and A375 melanoma cells, we observed increased pigmentation and increased expression of TRP1 and TRP2 at transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…By employing genome-wide analysis, Ren et al (2016) identified numerous lncRNAs associated with skin pigmentation in goats. Furthermore, evidence shows that lncRNAs can regulate melanogenesis via epigenetic regulation, while miRNAs can directly target many melanogenesis-related genes (Ho et al, 2020;review by Zhou et al, 2021). In aquaculture species, numerous significant differentially expressed lncRNAs (DElncRNAs) and miRNAs (DEmiRNAs) have been identified or further investigated by using different skin colors or other pigmented tissues in numerous species, such as Koi carp (Cyprinus carpio L.) (Luo et al, 2018(Luo et al, , 2019Dong et al, 2020;Yin et al, 2020), Pacific oyster (Crassostrea gigas) (Feng et al, 2018;Li Z. et al, 2021), red tilapia (Oreochromis sp.…”
Section: Introductionmentioning
confidence: 99%
“…By employing genome-wide analysis, Ren et al (2016) identified numerous lncRNAs associated with skin pigmentation in goats. Furthermore, evidence shows that lncRNAs can regulate melanogenesis via epigenetic regulation, while miRNAs can directly target many melanogenesis-related genes (Ho et al, 2020;review by Zhou et al, 2021). In aquaculture species, numerous significant differentially expressed lncRNAs (DElncRNAs) and miRNAs (DEmiRNAs) have been identified or further investigated by using different skin colors or other pigmented tissues in numerous species, such as Koi carp (Cyprinus carpio L.) (Luo et al, 2018(Luo et al, , 2019Dong et al, 2020;Yin et al, 2020), Pacific oyster (Crassostrea gigas) (Feng et al, 2018;Li Z. et al, 2021), red tilapia (Oreochromis sp.…”
Section: Introductionmentioning
confidence: 99%
“…Although some lncRNAs have been proven to participate in the regulation of pigmentation process, such as H19, UCA1, SPRIGHTLY, TUG1, TCONS_00049140, ENST00000606533, SRA, etc. [14][15][16][17][18][19][20], their number is small, and there are still many lncRNAs related to pigmentation waiting to be discovered. In this study, we detected the lncRNA profiles in black and white sheep skin and obtained 4,904 lncRNAs, among which 2,686 novel lncRNAs were identified.…”
Section: Discussionmentioning
confidence: 99%
“…ENST00000606533-miR-1291-TYR promotes melanogenesis [17], whereas SRA, UCA1 and TUG1 may negatively regulate melanogenesis in melanocytes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For intracellular experiments, the human melanocyte line that depends on the activation of TRY pathway is a key element in efficiently evaluating the anti-melanin synthesis effect of WFP. The A375 cell line, a metastatic cell line of the human amelanotic melanoma, has been widely used as a reliable model for screening anti-melanin agents [ 41 – 43 ], which is dependent on TRY pathway activation [ 44 , 45 ]. Firstly, thecytotoxic effect of WFPin A375 cells should be evaluated, and eliminate the influence caused by the decease of melanin synthesis due to cell numbers decline.…”
Section: Discussionmentioning
confidence: 99%